Serial sampling of copeptin levels improves diagnosis and risk stratification in patients presenting with chest pain: results from the CHOPIN trial. Issue 1 (23rd June 2015) - Marston, Nicholas A; Shah, Kevin S; Mueller, Christian; Neath, Sean-Xavier; Christenson, Robert H; McCord, James; Nowak, Richard M; Daniels, Lori B; Hollander, Judd E; Apple, Fred; Nagurney, John; Schreiber, Donald; et al.
Abstract : Background: Copeptin has demonstrated a role in early rule out for acute myocardial infarction (AMI) in combination with a negative troponin. However, management of patients with chest pain with a positive copeptin in the setting of a negative troponin is unclear. Methods: The multicentre CHOPIN trial enrolled 2071 patients with acute chest pain. Of these, 476 subjects with an initial negative troponin but an elevated copeptin (>14 pmol/L) were included in this study. Copeptin and troponin levels were rechecked at 2 h and the final diagnosis of AMI was made by two independent, blinded cardiologists. Follow-up at 30 days was obtained for major adverse cardiac events (MACEs), including death, AMI and urgent revascularisation. Results: Of the 476 patients analysed, 365 (76.7%) had a persistently elevated copeptin at 2 h and 111 patients (23.3%) had a copeptin that fell below the cut-off of 14 pmol/L. When the second copeptin was elevated there were 18 AMIs (4.9%) compared with 0 (0%) when the second copeptin was negative (p=0.017), yielding a negative predictive value of 100% (95% CI 96.7% to 100%). On 30-day follow-up there were 36 MACEs (9.9%) in the positive second copeptin group and 2 (1.8%) MACEs in the negative second copeptin group (p=0.006). Conclusions: Patients with chest pain with an initial negative troponin but positive copeptin are common and carry an intermediate risk of AMI. A second copeptin drawn 2 h after presentation may help risk stratify and potentially rule out AMI in this cohort.